Characterization of iron-sulfur clusters in flavin-containing opine dehydrogenase. Issue 12 (1st December 2016) - Watanabe, Seiya; Tajima, Kunihiko; Matsui, Kazuma; Watanabe, Yasuo
Abstract: Flavin-containing opine dehydrogenase from Bradyrhizobium japonicum forms a heterooligomeric α4 β4 γ4 enzyme complex. An electron paramagnetic resonance spectroscopy analysis using wild-type and site-directed mutants revealed that [4Fe-4S] and [2Fe-2S] clusters bind to two different types of [Fe-S] binding sites in the γ- and α-subunits, respectively. The latter was found to be important for structural folding and enzyme catalysis.